The role of the religious complex of Ukraine in the processes of social change: dynamics of public perceptions - Victor Voinalovich (Політичні дослідження, 2022)
The article analyzes the dynamics of public perceptions of the role of religion and religious institutions of Ukraine in the processes of social changes during 2014−2021. The empirical basis of the study is the results of the constant sociological monitoring of the state and trends of religiosity of Ukrainian society, the level of public trust in the church as a social institution, as well as public opinion on the role of religion and the church in public life, which has been carried out by the Razumkov Center since 2000. The topicality of the problem is argued by the natural dynamism and changeability of the religious environment, its constant and obvious institutional and identificational changes, on the one hand, and the traditional influence of the religious complex on the course of socio-political transformations in modern Ukraine, on the other. Attention is focused on the importance of diagnosing public reflections on the role of religion and religious organizations in the processes of social changes as a prerequisite for scientific analysis of existing practices of socio-religious interactions and their further forecasting.It is emphasized that religion and religious organizations rarely act as independent agents of social changes, and are only one of several active ones because the social behavior of individuals is determined not only by religious motives. Factors that had a decisive influence on the formation of public perceptions in the post-war period were the results of transformational changes in the domestic religious complex, which occurred primarily under the influence of the Revolution of Dignity (2013−2014), the annexation of the Autonomous Republic of Crimea, the ongoing armed conflict in the East of the country, the large-scale war against Ukraine launched by Russia (since February 2022) and, of course, the processes related to the granting of autocephaly to Ukrainian Orthodoxy and the election campaigns of the President of Ukraine to the Verkhovna Rada of Ukraine (2019).It is proved that the above-mentioned processes determine the obvious variability and ambivalence perceptions of citizens about the role of religion and the church in public life.Traditionally, the high level of declared religiosity of Ukrainian citizens is combined with a low degree of their real religious activity. The relatively high and stable level of trust in the church is discordant with the steady decline in recognition of its role as a moral authority. Remaining generally tolerant of the practice of different religions, Ukrainian citizens declare rather different assessments of their attitude to the most widespread religions and religious organizations in Ukraine. Despite a certain increase in the positive assessment of the role of religious institutions, more than a third of respondents emphasize the absence of their significant role. Public opinion also declares significant reservations about the adequacy of the response of the largest churches to current challenges and problems of society.It is argued that the definition of the role of religion and religious institutions in the processes of social changes in Ukraine does not have an unambiguous dimension and under certain circumstances, religion can act both as a factor of national and social reconciliation and consolidation, and as a catalyst for social upheaval.